Effect of telmisartan on functional outcome, recurrence, and blood pressure in patients with acute mild ischemic stroke: a PRoFESS subgroup analysis - Bath, Philip M.W.; Martin, Renée H.; Palesch, Yuko; Cotton, Daniel; Yusuf, Salim; Sacco, Ralph L.; Diener, Hans-Christoph; Toni, Danilo; Estol, Conrado; Roberts, Robin (American Heart Association Inc, 2009)
Background and Purpose—High blood pressure (BP) is common in acute ischemic stroke and associated independently with a poor functional outcome. However, the management of BP acutely remains unclear because no large trials have been completed.